Implikasi Hukum Islam Dari Putusan Pengadilan Negeri Balikpapan Tentang Pencatatan Pernikahan Beda Agama - Maesaroh, Siti; Yuni, Lilik Andar (Universitas Cokroaminoto Yogyakarta, 2024)
This study discusses interfaith marriages which have become an undeniable controversy in Indonesia with its religious diversity. Article 35a of the Population Law Number 23 of 2006 is the basis for regulating heterosexual marriages in order to obtain permission to conduct interfaith marriages and instruct the local population and civil registry office to make records. In decision No. 220/Pdt.P/2021/PN Bpp, for example, the judge permitted interfaith marriages by considering several applications, administrative files and witnesses brought by the applicant. The research method used is the normative legal approach method, namely a method that is a library legal research. The results of the study show that the Qur'an, Surah Al-Baqarah verse 221, clearly prohibits a group of people from carrying out interfaith marriages, however, in Law No. 1 of 1974, one of the judge's considerations in the Balikpapan District Court Decision Number 220. Registration of interfaith marriages involves the results of a decision from the district court so that it can be recorded by the local population and civil registry office.